Edukasi gizi seimbang, penilaian status gizi dan kualitas hidup lansia - Tingginehe, Rosmin Mariati; Pariaribo, Konstantina; Zamuli, Habibi (Jurnal PADE: Pengabdian & Edukasi, 2024)
The elderly are a vulnerable group that often faces nutritional problems and a declining quality of life, especially in remote areas such as Keerom Regency. The lack of balanced nutrition education and inadequate health interventions are the main challenges in improving the well-being of the elderly. This community service activity aims to fill that gap by enhancing the elderly's knowledge about balanced nutrition, assessing their nutritional status, and evaluating their quality of life at Yaturaharja Posyandu, within the work area of Arso Barat Health Center. Nutrition education was provided through a question-and-answer method and interactive games to ensure active participation of the elderly. In addition, nutritional status was assessed using anthropometric measurements, and quality of life was evaluated using the WHOQOL-BREF questionnaire, which covers four domains: physical health, psychological well-being, social relationships, and environment. Out of 120 registered elderly, 54 participated in the activity. The results showed that the elderly's knowledge of balanced nutrition remained low, with 70% of participants unable to answer questions correctly. Furthermore, 70% of the elderly had a low Body Mass Index (BMI), indicating malnutrition problems. While the physical health and environmental aspects were relatively good, social relationships remained a challenge for the majority of the elderly. This activity highlights the importance of sustainable interventions, with practical recommendations such as continued nutrition education, additional nutritional interventions, and enhancing social activities for the elderly. Cross-sector collaboration is expected to strengthen this program and improve the quality of life for the elderly in the future.